Leech’s Politeness Principle in KPU Officials’ Public Speech: A Pragmatic Study - Perla Yualita; Siti Maryam Maulida; Maratushshalihah Maratushshalihah; Andoyo Sastromiharjo (SAWERIGADING, 2026)
This study aims to analyze the application of Geoffrey Leech’s Politeness Principle in the public speeches of officials from the General Elections Commission (KPU) and to explain the pragmatic functions of politeness in institutional public communication. This research employed a qualitative descriptive approach within a pragmatic framework. The data consisted of utterances produced by KPU officials obtained from official press conference transcripts from 2019–2025. Data were collected through documentation and note-taking techniques. The data were analyzed using content analysis through data reduction, categorization based on Leech’s politeness maxims, and pragmatic interpretation of the speech context. The findings reveal that the speeches of KPU officials were predominantly characterized by the tact maxim, approbation maxim, and modesty maxim. In addition, the study identified the use of indirectness strategies and politeness implicatures to reduce conflict, maintain social relations, and strengthen public trust. The utterances of KPU officials also demonstrate the interrelationship between politeness principles, speech acts, and facework strategies in maintaining institutional image and legitimacy. Therefore, Leech’s Politeness Principle proves to be relevant as a pragmatic framework for understanding ethical, persuasive, and legitimacy-oriented institutional communication.  AbstrakPenelitian ini bertujuan untuk menganalisis penerapan prinsip kesantunan Geoffrey Leech dalam tuturan pejabat Komisi Pemilihan Umum (KPU) pada konferensi pers resmi serta menjelaskan fungsi pragmatik kesantunan dalam komunikasi institusional publik. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan kajian pragmatik. Data penelitian berupa tuturan pejabat KPU yang diperoleh dari transkrip konferensi pers resmi KPU Periode 2019-2025. Teknik pengumpulan data dilakukan melalui dokumentasi dan pencatatan tuturan. Teknik analisis data menggunakan analisis isi melalui tahapan reduksi data, kategorisasi berdasarkan maksim kesantunan Leech, dan interpretasi pragmatik terhadap konteks tuturan. Hasil penelitian menunjukkan bahwa tuturan pejabat KPU didominasi oleh maksim kearifan (tact maxim), maksim penghargaan (approbation maxim), dan maksim kerendahan hati (modesty maxim). Selain itu, ditemukan penggunaan strategi ketidaklangsungan (indirectness) dan implikatur kesantunan untuk meredam konflik, menjaga hubungan sosial, serta membangun kepercayaan publik. Tuturan pejabat KPU juga memperlihatkan keterkaitan antara prinsip kesantunan, tindak tutur, dan strategi facework dalam mempertahankan citra kelembagaan. Dengan demikian, prinsip kesantunan Leech terbukti relevan sebagai kerangka pragmatik untuk memahami komunikasi institusional yang etis, persuasif, dan berorientasi pada legitimasi publik.